Speech Therapy and Earnings: Economic Benefits for Individuals Who Stutter - Briley, Patrick M.; Jacobs, Molly M. (Seminars in Speech and Language, 2022)
Stuttering is a complex communication disorder with effects that extend beyond difficulty with communication. Negative thoughts and feelings by the person who stutters (PWS), about the disorder or themselves, may potentially lead to detrimental avoidance behaviors which may ultimately alter life choices and participation in life events. One such area is the labor market. Studies have revealed an association between stuttering and reduced earnings. What is not understood is whether provision of speech therapy for PWS can help mitigate the negative labor market impacts of this condition. This article discusses the disorder of stuttering and how approach versus avoidance responses can contribute to wage differentials among PWS, while also providing evidence of such differences using a nationally representative dataset. Additionally, this article outlines the potential benefits received from speech-language pathology services which may correlate with improved labor market outcomes.
Keywords: stuttering; speech therapy; income